The dimensions of interpersonal communication competence: an analysis of data collected by multiple self-rating scales - Bubaš, Goran (1999)
The dimensions of interpersonal communication competence are investigated, as well as the relations of those dimensions with the "big-five" model of personality. A research instrument named Interpersonal Communication Competence Inventory (ICCI) was constructed. It consisted of 374 items distributed in 23 scales designed to measure various constructs related to interpersonal communication competence. The ICCI was applied on two groups of subjects (N1=136 and N2=418). Several other self-rating assessment instruments were applied on most of the subjects of the first group. The results revealed two basic dimensions of interpersonal interactions: (1) communicative effectiveness and (2) other-orientedness. Further factor analyses uncovered four more possible dimensions of interpersonal communication competence that were named: (3) decoding and encoding, (4) social relaxation, (5) expressivity, and (6) intentionality. Structural relations of the dimensions of interpersonal communication competence were also discovered with the following five basic dimensions of personality: extraversion, agreeableness, openness to experience, neuroticism, and conscientiousness.